Minimally invasive surgery improves outcome of left ventricular assist device surgery in cardiogenic shock - Wert, Leonhard; Chatterjee, Anamika; Dogan, Günes; Hanke, Jasmin S.; Boethig, Dietmar; Tümler, Kirstin A.; Napp, L. Christian; Berliner, Dominik; Feldmann, Christina; Kuehn, Christian; Martens, Andreas; Shrestha, Malakh L.; et al. (Journal of Thoracic Disease, 2018)
Background: Left ventricular assist device (LVAD) (HVAD, Medtronic, Minneapolis, MN, USA) implantation is already a widely accepted treatment option for end-stage heart failure (HF) but also still considered as a rescue therapy for patients suffering from cardiogenic shock. Standard LVAD implantation techniques are often associated with high mortality rates and can result in severe complications, like bleeding or right heart failure (RHF). The aim of our study was to assess the outcome of Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) 1 patients (so called “crash and burn” patients) undergoing a LVAD implantation by standard or less invasive surgery. Methods: We performed a retrospective evaluation of the 1-year outcome of 32 consecutive HF patients in cardiogenic shock, who underwent LVAD implantation in our institution. A total of 32 INTERMACS 1 patients were emergently operated. Fourteen patients (group A) were operated by using the “Hannover-VAD-technique”, which is widely known to be less invasive (upper hemisternotomy and a left-sided anterolateral thoracotomy). In contrast, 18 patients (group B) were implanted with LVAD by using the standard technique (full sternotomy). The primary endpoint was survival after 1 year without device-related re-operations. Secondary endpoints included combined analyses of rates of RHF, respiratory failure and bleeding during the trial period. Results: Baseline characteristics were similar in both groups. Survival after 1 year was higher in group A (69.7% vs. 50.0%). Technique-related adverse events (AEs) were also lower in the minimally invasive group, including a lower RHF (35.7% vs. 61.1%) and of further postoperative bleeding requiring surgery (14.3% vs. 33.3%). Conclusions: LVAD surgery in INTERMACS 1 patients is associated with remarkably good outcome considering the already very high mortality of those patients, and compared to previously reported surgical outcomes. Our study indicates that minimally invasive LVAD implantation in cardiogenic shock decreases mortality and the incidence of postoperative AEs.